Implications of childhood obesity for adult health: findings from thousand families cohort study. Issue 7324 (1st December 2001) - Wright, Charlotte M; Parker, Louise; Lamont, Douglas; Craft, Alan W
Abstract: Objective: To determine whether being overweight in childhood increases adult obesity and risk of disease. Design: Prospective cohort study. Setting: City of Newcastle upon Tyne. Participants: 932 members of thousand families 1947 birth cohort, of whom 412 attended for clinical examination age 50. Main outcome measures: Blood pressure; carotid artery intima-media thickness; fibrinogen concentration; total, low density lipoprotein, and high density lipoprotein cholesterol concentrations; triglyceride concentration; fasting insulin and 2 hour glucose concentrations; body mass index; and percentage body fat. Results: Body mass index at age 9 years was significantly correlated with body mass index age 50 ( r =0.24, P<0.001) but not with percentage body fat age 50 ( r =0.10, P=0.07). After adult body mass index had been adjusted for, body mass index at age 9 showed a significant inverse association with measures of lipid and glucose metabolism in both sexes and with blood pressure in women. However, after adjustment for adult percentage fat instead of body mass index, only the inverse associations with triglycerides (regression coefficient= −0.21, P<0.01) and total cholesterol (−0.17, P<0.05) in women remained significant. Conclusions: Little tracking from childhood overweight to adulthood obesity was found when using a measure of fatness that was independent of build. Only children who were obese at 13 showed an increased risk of obesity as adults. No excess adult health risk from childhood or teenage overweight was found. Being thin in childhood offered no protection against adult fatness, and the thinnest children tended to have the highest adult risk at every level of adult obesity.